Molecular mechanism of the ichthyosis pathology of Chanarin–Dorfman syndrome: Stimulation of PNPLA1-catalyzed ω-O-acylceramide production by ABHD5. Issue 3 (December 2018) - Ohno, Yusuke; Nara, Atsuki; Nakamichi, Shota; Kihara, Akio
Highlights: ABHD5 enhances PNPLA1-dependent acylceramide synthesis. ABHD5 recruits PNPLA1 to the lipid droplet membrane or its periphery. Co-expression of ABHD5 and PNPLA1 causes disappearance of lipid droplets. Chanarin–Dorfman syndrome-causative mutations reduce ABHD5 activity. Abstract: Background: ABHD5 mutations cause Chanarin–Dorfman syndrome accompanied by ichthyosis. ω- O -Acylceramide (acylceramide) is essential for skin permeability barrier formation. Acylceramide production is impaired in Abhd5 knockout mice. The transacylase PNPLA1 catalyzes the final step of acylceramide production: transfer of linoleic acid in triglyceride to ω-hydroxyceramide. Objective: We aimed to elucidate the role of ABHD5 in acylceramide production and the molecular mechanism of the ichthyosis symptoms of Chanarin–Dorfman syndrome. Methods: We investigated how ABHD5 influences acylceramide production using an acylceramide-producing cell system. The effects of ABHD5 and PNPLA1 expression on the morphology of lipid droplets were examined by indirect immunofluorescent microscopy and immunoelectron microscopy. Results: When ABHD5 was expressed in the acylceramide-producing cell system, acylceramide synthesis by PNPLA1 was enhanced. Dispersed localization of PNPLA1 was observed by immunofluorescent microscopy in HeLa cells under lipid droplet-forming conditions. Co-expression with ABHD5 caused PNPLA1 to localize on the lipid droplet membranes or their periphery. This staining pattern was observed in cells where PNPLA1 and ABHD5 were expressed at low levels. In contrast, lipid droplets disappeared in cells where PNPLA1 and ABHD5 were highly expressed. Immunoelectron microscopic analyses suggested that lipid droplets underwent morphological changes, transforming into vesicles or becoming incorporated into the endoplasmic reticulum. ABHD5 mutations found in Chanarin–Dorfman syndrome patients reduced ABHD5's ability to promote PNPLA1-dependent acylceramide production. Conclusion: ABHD5 enhances PNPLA1-catalyzed acylceramide production. We speculate that ABHD5 retains triglycerides in the endoplasmic reticulum, and presents them to PNPLA1 to promote substrate recognition.